Analysis of Politeness in Language at Talkshow Shows Try Face-to-Face in Najwa's Eyes on Youtube - Indah Nurfitriyani; Intan Sari Ramdhani (AURELIA: Jurnal Penelitian dan Pengabdian Masyarakat Indonesia, 2023)
This study aims to examine the principles and violations of politeness in language talk shows try to face-to-face in Mata Najwa broadcasts on YouTube. In this study, researchers used a qualitative approach and used descriptive methods. The subject of the research is speech on talk shows, try face-to-face in Najwa's eyes on YouTube. Research subjects were obtained through you tube social media. Meanwhile, the object of this study is polite speech. Data collection techniques in this study using documentation techniques. The instrument in this study is a data card. The collected data were analyzed using a qualitative descriptive analysis. Data analysis in this study used qualitative data analysis procedures, namely (1) data reduction, (2) data presentation, (3) drawing conclusions. The results of this study found the principles and violations of politeness in the talk show, try to meet face to face in Mata Najwa's broadcast on YouTube. , the maxim of sympathy, the maxim of humility, the maxim of generosity or the maxim of generosity. (2) In addition, there are violations or deviations from the politeness principle in the form of violations of the maxim of wisdom, violation of the maxim of praise, violation of the maxim of sympathy and violation of the maxim of humility. The conclusion of this study is the results of an analysis of language politeness on talkshows, try face-to-face in Najwa's eyes on YouTube.